Comparison of Epidemiological data from Switzerland and Germany – Part 2 - Rychlik, Reinhard; Thiem, Helena; Kunde, Katharina; Völkel, Lukas; Kremer, Alexander; Ackermann Rau, Sabine; Schneiter, Jonas (Gesundheitsökonomie & Qualitätsmanagement, 2025)
The epidemiological and health statistical comparison of the populations of Germany and Switzerland on the basis of various parameters shows a very similar population structure. This can be seen primarily in the age and gender structure of both populations, which are almost identically distributed. This generally enhances the informative value of the parameters compared. Challenges in the comparison of the data were primarily identified as different survey dates, a different population under consideration, and, for individual disease patterns, the collection of different parameters within the two countries. Since some sources were surveys, a bias of the results due to the subjective assessment of the participants cannot be excluded.
Keywords: Switzerland; Germany; epidemiology; health statistics